Associations between knowledge on optimal control of serum phosphate, perceived social support, dietary phosphorus intake and phosphate compliance among hemodialysis patients - Mohd Isa, Muhammad Darwish Asyraf; Lai, Fiona Jie Wei; Chong, Shen Yi; Ismail, Nur Amrina Rasyada; Chan, Kar Fei; Chan, Yoke Mun (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Hyperphosphatemia is common among hemodialysis patients, often accompanies with unfavourable clinical outcomes. Several factors affect phosphate compliance among hemodialysis patients, with lack of such information at the local context. Thus, this cross-sectional study aimed to determine the associations of sociodemographic factors, knowledge on optimal control of serum phosphate, perceived social support from family, dietary phosphorus intake and phosphate compliance among hemodialysis patients. Methods: Structured questionnaire was used to obtain information on socioeconomic factors, knowledge, family social support and dietary phosphorus intakes of hemodialysis patients, with serum phosphate level was used as the surrogate marker for phosphate compliance. Results: A total of 76 patients (Mean age of 52 years old) were recruited. Hyperphosphatemia was prevalent with approximately 60% of the patients failed to achieve the target. Approximately 90% of the patients perceived low level of family social support. Young patients had significant higher serum phosphate compared to their older counterparts (r = -0.297, p =0.009). Serum phosphate was positively correlated with dietary intake of phosphorus, dialysis vintage (r = 0.301, p = 0.006) and comorbidity score (r = 0.325, p = 0.008) while negatively correlated with dialysis dose (r = -0.582, p = 0.002) and family social support (r = -0.263, p = 0.024). Conclusion: The promising role of dietary phosphorus intake in managing hyperphosphatemia deserves further attention. Innovative approaches are needed to promote self-adherence on serum phosphate especially the younger patients. It is imperative to promote family social support in the management of hyperphosphatemia among hemodialysis patients.